IMPLEMENTATION OF COOPERATIVE LEARNING MODEL TYPE OF TPS BASED SAVI TO COMPLETE STUDENT LEARNING OUTCOME - iva septy wulandari; Muchlis Muchlis (JCER (Journal of Chemistry Education Research), 2020)
This study aims to describe the implementation, activities, learning outcomes, and student responses after the application of SAVI type TPS-based cooperative learning models of electrolyte and non-electrolyte solution materials. This study uses "one group pretest-posttest design". The implementation of SAVI-based TPS type cooperative learning model with an average value of 3.31 and 3.78 in the excellent category. Somatic student activity at 20.53% at the first meeting and 17.83% at the second meeting, intellectual students at 12.35% at the first meeting and 11.7% at the second meeting, auditory students at 11.7% at the first meeting and 11, 7% the second meeting, visual students by 11.58% at the first meeting and 10.88% the second meeting. This shows that students have a relevant percentage of time in accordance with the learning style with the type of cooperative learning model TPS. Complete learning outcomes of all students by 94% at the first meeting and 97% at the second meeting. Student responses after SAVI-based TPS type cooperative learning were very good with a percentage of positive responses of 98.61%.  Keywords: Cooperative, TPS, SAVI, learning outcomes, response.